Die dogmatische Stelle und die Rolle des Kindesalters in der modernen ungarischen Rechtsentwicklung - Balogh, Ágnes Rózsa (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
According to the provisions of the Criminal Code in force, in the case of violent offenses listed in the law, young offenders aged 12-14 who have the ability to recognize the consequences of a crime may be punished as well. Ability of discernment is not a new concept in our criminal law; this study describes the change in the content of this concept and the development of the criminal regulations on childhood, referring to the practical problems of applying the law in force.